ENGLISH COMMUNICATION SKILLS OF FRONT OFFICE STAFFS IN KENDARI : STUDY CASE - Ulumuddin, Ihya; Indah, Tri Rusli; Nasrullah, Rahmat (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study investigates the English communication skills of Front Office staff in Kendari, Southeast Sulawesi, by examining the gap between theoretical linguistic competence and actual professional performance. Utilizing a case study design with a Convergent Parallel Mixed-Methods approach, data were triangulated from CEFR-based assessments, field observations, and in-depth interviews across five practitioners. The findings reveal that while linguistic proficiency ranges from A2 to C1 levels, professional success is primarily driven by functional pragmatism and compensatory strategies rather than mere grammatical accuracy. The research identifies critical hurdles such as Foreign Language Anxiety (FLA), physical fatigue from shift rotations, and phonological barriers (accents), which often lead to a